(Re)Introducing Vygotsky’s Thought: From Historical Overview to Contemporary Psychology - Vasileva, Olga; Balyasnikova, Natalia (Frontiers in Psychology, 2019)
Theories formulated by Russian psychologist and educator Lev Vygotsky currently range from being applied and celebrated across multiple contexts to be considered outdated. In this paper, we maintain that such inconsistency in application stems from the overreliance on translated or reformulated Vygotskian theories, the attempts to understand these ideas in isolation from the scientific historical context of their development, and the impact of Vygotsky’s personal life circumstances on the development of his scholarship. It is known that Vygotsky’s untimely death prevented him from elaborating on his theoretical views and expanding his early empirical work. We suggest that Vygotsky’s scholarship could be better understood in light of the core principles that transcend all aspects of his work. In this paper, we elaborate on two such core principles: theories of language development and their relation to the integrated systemic approach to psychological development. We argue that although linguistic and historical boundaries have shaped the common perception of Vygotskian theories in anglophone research in a specific way, there is a potential for a renewed application of these theories to modern psychology that might be especially relevant in light of the increasingly interdisciplinary character of the modern science. To support our argument, we provide a brief overview and examples of potential connections between Vygotsky’s scholarship with contemporary landscape in psychological science. The paper presents a brief introduction to the topic of Vygotskian work and its application to modern psychology, rather than an addition to the field of Vygotskian scholarship. It is geared towards non-Vygotskian scholars and invites researchers working in interdisciplinary areas of psychology.